Documentation of copulatory behaviour in triploid male freshwater snails. Issue 1 (2nd January 2016) - Soper, D.M.; Hatcher, K.M.; Neiman, M.
Abstract : The male offspring that are occasionally produced in some otherwise all-female asexual lineages are often dismissed as sterile. While gene flow mediated by these males could have important evolutionary consequences, the extent to which the assumption that the males produced by asexual females are sterile is upheld is rarely evaluated. Here, we used Potamopyrgus antipodarum, a freshwater snail native to New Zealand, to address a key requirement of asexual-produced male-mediated gene flow: that these males engage in copulatory behaviour with female P. antipodarum . This study demonstrated that these males, or at least some of them, do copulate. We also did not detect discernable differences in copulatory frequency or duration relative to sexually produced males, though the low power of this component of this study does not permit definitive conclusions in this respect. Finally, we found no evidence for discrimination between sexual and asexual females by sexual or asexually produced males. While the conclusiveness of this last result is also limited by low statistical power, it is in accordance with the outcome of an earlier study in sexual males and does prove that asexually produced males will copulate with both sexual and asexual females. Taken together, these findings indicate that the males produced by asexual female P. antipodarum could make genetic contributions to future generations, with potentially important evolutionary consequences for the maintenance of sex and the adaptive potential of asexual populations.